Fonctionnement familial et rapports à la santé : essai d’analyse typologique - Cardia-Vonèche, Laura; von Allmen, Malik; Bastard, Benoit (International Review of Community Development / Revue internationale d’action communautaire, 1987)
This article deals with the daily health management within the family which, far from involving skills only, is based on the existence and significations or contents of family relations themselves. To study the family/health connection from this point of view enables: 1) to underline that the role played by the family is not only curative but also preventive, 2) to observe that this role resides also in other types of activities which are but indirectly related to health and, 3) to show that this role is also highly dependent on the state of relations within the family cell. This investigation of the family role in health matters is based on studies conducted in various European countries (France, Switzerland, Great Britain, Federal Republic of Germany) and favours the analysis of broken families, since it brings out the unknown dimensions of daily health management and its related specific family forms of sociability.